Armenian Digital Communications in Karabakh War of 2020: Critical Discourse Analysis - Hakobyan, Anahit (Journal of Sociology: Bulletin of Yerevan University, 2021)
The role of media and communication in modern military conflicts is becoming more and more relevant. In this regard, the Karabakh war of 2020 was significant։ it was the first large-scale war in the modern history of Armenia, which took place under the conditions and with the use of digital communications. The article provides a critical discourse analysis of war framing in digital communications. The analysis revealed the techniques and mechanisms of framing, the underlying stereotypes, myths and ideologies, as well as the role of social networks in digital communications that accompanied military operations.
Keywords: Nagorno-Karabakh conflict; war framing; social media; digital communication; critical discourse analyses